EFISIENSI ENERGI TERMAL SISTEM BOILER DI INDUSTRI - Achmad Hasan (Badan Pengkajian dan Penerapan Teknologi, 2008)
Energy efficiency is one way to plan for optimizing the supply and use of energyneeded by the industry. Supplies of gas / diesel fuel oil for boiler feed of 1.4537million m3 per year with a calorific value of 6 tons / hour and 900 liters of diesel oilper year. Thermal energy used in the production process in industry (in case:PT.Classic Prima Carpet Industries) divided into thermal energy in the form of hotwater vapor (steam) and the other in the form of natural gas. Energy is producedfrom 2 (two) units of gas boilers and steam boilers each with a capacity of 6 tons/ hour, in which the steam boiler in a state of stand-by and operated only whenproduction increases.Kata kunci: energi, efisiensi, termal, boiler, penghematan, konversi, konservasi